2021
DOI: 10.1097/mpg.0000000000003067
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Bile Acid Metabolism in Pediatric Diarrhea Predominant Irritable Bowel Syndrome and Healthy Controls

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 46 publications
(82 reference statements)
1
10
0
Order By: Relevance
“…Previous studies revealed that intestinal microflora play a key role in maintaining metabolic balance ( 40 ). Most of metabolites in the blood were used to as biomarkers for diarrhea-related diseases ( 41 ). Thus, to study the fecal microbiota composition and plasma metabolomics characteristics of DHD calves may help to understand the pathogenesis of DHD and develop appropriate intervention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that intestinal microflora play a key role in maintaining metabolic balance ( 40 ). Most of metabolites in the blood were used to as biomarkers for diarrhea-related diseases ( 41 ). Thus, to study the fecal microbiota composition and plasma metabolomics characteristics of DHD calves may help to understand the pathogenesis of DHD and develop appropriate intervention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that, after early childhood, the ability to synthesize BAs and the patterns of BAs in children and adolescents are similar to those found in adults 7,8 …”
Section: Introductionmentioning
confidence: 86%
“…45 Given that it is estimated that 5% of the population in developed countries has chronic diarrhea of >4 weeks' duration at any point in time 46 and that BAD affects at least 25% of patients with chronic diarrhea, 18 it was proposed that ~1% of adults in Western countries have BAD. 47 Adolescents: In a cross-sectional study of adolescents 7 b. Post-cholecystectomy: A systematic review of 25 studies that included 3,388 patients showed only 9.1% of patients developed diarrhea after cholecystectomy, with two-thirds associated with evidence of BAD. 51 Similarly, in 125 consecutive patients who underwent laparoscopic cholecystectomy, 25.2% developed diarrhea at one week after surgery and 5.7% had diarrhea at 3 months.…”
Section: Epidemiology Of Idiopathic Bad and Associations With Other I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Using serum 7αC4 measurements, a two-center USA study [10] reported BAD in 20% of adolescents with irritable bowel syndrome with diarrhea (IBS-D), based on the 95th percentile value of 54.0 ng/mL among 56 healthy adolescents. The ULN for serum 7αC4 in adults and adolescents in the USA was similar (adolescents 54.0 ng/mL, adults 52.8 ng/mL); moreover, 28% of adolescents with IBS-D had low FGF19 values.…”
mentioning
confidence: 99%